2020
DOI: 10.1161/strokeaha.120.030335
|View full text |Cite|
|
Sign up to set email alerts
|

SARS-CoV-2 and Stroke in a New York Healthcare System

Abstract: Background and Purpose: With the spread of coronavirus disease 2019 (COVID-19) during the current worldwide pandemic, there is mounting evidence that patients affected by the illness may develop clinically significant coagulopathy with thromboembolic complications including ischemic stroke. However, there is limited data on the clinical characteristics, stroke mechanism, and outcomes of patients who have a stroke and COVID-19. Methods: We conducted a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

61
769
17
37

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 639 publications
(884 citation statements)
references
References 17 publications
61
769
17
37
Order By: Relevance
“…They recommended monitoring of prothrombin time, Ddimer, platelet count, and fibrinogen and prophylactic anticoagulation with low-molecular weight (LMW) heparin in all patients with COVID-19. Yaghi et al [6] reported that high levels of D-dimer were more common among patients with stroke and COVID-19 and suggested that hypercoagulability may underly much of stroke in this disease. They indicated that a randomized trial of therapeutic anticoagulation versus prophylactic anticoagulation is underway.…”
Section: Hypercoagulable Statementioning
confidence: 99%
See 3 more Smart Citations
“…They recommended monitoring of prothrombin time, Ddimer, platelet count, and fibrinogen and prophylactic anticoagulation with low-molecular weight (LMW) heparin in all patients with COVID-19. Yaghi et al [6] reported that high levels of D-dimer were more common among patients with stroke and COVID-19 and suggested that hypercoagulability may underly much of stroke in this disease. They indicated that a randomized trial of therapeutic anticoagulation versus prophylactic anticoagulation is underway.…”
Section: Hypercoagulable Statementioning
confidence: 99%
“…An early report from China and the previous report from Singapore on SARS-CoV-1 infection developing stroke during that 2002-2003 outbreak demonstrated cardioembolic mechanisms in 36 and 60% of their cases, respectively [43]. Yaghi et al [6] reported that stroke patients with COVID-19 were more likely to be young men with elevated troponin levels compared with historical controls.…”
Section: Cardiomyopathymentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of patients with previous arterial hypertension was similar in both studies. In regard to age, a case series of ve COVID-19 ischemic stroke patients with a lower age (ranged between 33 and 49 years) remains outstanding[38].In comparison to our meta-analysis, Yaghi et al described a lower rate of ischemic strokes in patients with COVID-19 infections in New York City with a follow-up of up to four weeks[39]. Referring to 3,556 hospitalized COVID-19 patients, the researchers reported 32 patients with COVID-19 that suffered from an ischemic stroke.…”
mentioning
confidence: 49%